2020
DOI: 10.1021/acs.jmedchem.0c01019
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Roblitinib (FGF401) as a Reversible-Covalent Inhibitor of the Kinase Activity of Fibroblast Growth Factor Receptor 4

Abstract: FGF19 signaling through the FGFR4/β-klotho receptor complex has been shown to be a key driver of growth and survival in a subset of hepatocellular carcinomas, making selective FGFR4 inhibition an attractive treatment opportunity. A kinome-wide sequence alignment highlighted a poorly conserved cysteine residue within the FGFR4 ATP-binding site at position 552, two positions beyond the gate-keeper residue. Several strategies for targeting this cysteine to identify FGFR4 selective inhibitor starting points are su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 78 publications
1
87
0
Order By: Relevance
“…Our result is supported by a recent study that demonstrated significant benefits of EP300/CBP inhibitors in AR--positive BRCA and AR-positive PRAD cell lines with negligible effects on IC50’s for AR--negative cancers 66 . We also identified FGFR4 in LIHC with recent studies showing strong evidence to suggest the efficacy of an inhibitor, Roblitinib, in vitro and in vivo with xenograft models providing strong support to our results 67 . We find other chromatin modulators such as BRD7 in low grade glioma (LGG), BRD9 in Liver/Hepatocellular carcinoma (LIHC) and KDM5A in TGCT, KDM1A, KDM4A, KMT5B and KDM5C in PRAD as high priority druggable genes.…”
Section: Resultssupporting
confidence: 87%
“…Our result is supported by a recent study that demonstrated significant benefits of EP300/CBP inhibitors in AR--positive BRCA and AR-positive PRAD cell lines with negligible effects on IC50’s for AR--negative cancers 66 . We also identified FGFR4 in LIHC with recent studies showing strong evidence to suggest the efficacy of an inhibitor, Roblitinib, in vitro and in vivo with xenograft models providing strong support to our results 67 . We find other chromatin modulators such as BRD7 in low grade glioma (LGG), BRD9 in Liver/Hepatocellular carcinoma (LIHC) and KDM5A in TGCT, KDM1A, KDM4A, KMT5B and KDM5C in PRAD as high priority druggable genes.…”
Section: Resultssupporting
confidence: 87%
“…THNs feature prominently as arginine mimics in αv integrin inhibitors (e.g., 23 ), 47 and the THN scaffold has also been deployed as a semi-saturated bioisostere of a quinoline, to enhance compound solubility (e.g., 24 ). 48 …”
Section: Resultsmentioning
confidence: 99%
“… Fairhurst et al (2020) reported the discovery of FGF401 (roblitinib) as a potent, selective FGFR4 inhibitor. Through high throughput screening, 2-formylquinoline amide (2-FQA) derivatives were identified as the starting hits.…”
Section: Small-molecule Fgfr Inhibitorsmentioning
confidence: 99%